Global trends from original research on COVID-19 and coinfection - Moura, Maria Eliete Batista; Sousa Neto, Antonio Rosa de; Chissamba, Rogério Epolua; Carvalho, Ana Raquel Batista de; Peres, Neris Violeta Gonzalez; Oliveira, Thais Alexandre de; Valle , Andreia Rodrigues Moura da Costa; Freitas, Daniela Reis Joaquim de (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: The clinical symptomatology of SARS-CoV-2 and the occurrence of coinfections can be masked by the similarity of the manifestations, thereby delaying the clinical diagnosis and therapeutic decision-making, favoring the worsening of the clinical condition and increasing the chances of death. Aim: to conduct a bibliometric analysis of the world's scientific production on COVID-19 and coinfection in general. Outlining: Bibliometric study with a quantitative approach. Two hundred eight articles were analyzed using the Bibliometrix R package and the Biblioshiny application. Results: The articles were published mainly in 2021 and 2022. The scientific journals that published the most were the Journal of Medical Virology and Cureus. The most cited was the Journal of Medical Virology. The articles were cited 2567 times and addressed the etiology of coinfections, which bacteria, other viruses, fungi, and vectors can cause. Implications: Through this bibliometric analysis, it was possible to identify global trends in research on COVID-19 and coinfection, which in the long term can support the development of new research and the elaboration of strategies aimed at preventing, controlling, and managing cases of coinfections, not only in the pandemic period but continuously.